Perancangan User Experience Aplikasi Mobile Pelayanan Kependudukan Terpadu Kota Malang Menggunakan Metode Human Centered Design - Ferdinan Oky Fahrerri; Herman Tolle; Ratih Kartika Dewi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Dispendukcapil is the agency that handles the creation of population files and civil registration for Malang City. In its implementation, there are still deficiencies in the process of file processing at the Malang City Administration, causing many complaints from the public. Starting from the relatively long service time, complicated management process, no estimated completion time, to complaints from the public that they have to frequently come to the Dispendukcapil office to find out whether the population files being managed have been completed. Dispendukcapil once issued a birth certificate service application in 2018. However, until 2020 only five people were registered to have registered for birth certificates through the application due to difficulties. So that this integrated population service application requires a User Experience (UX) design so that people can use it easily and efficiently. The approach used in designing this application is Human Centered Design (HCD). HCD is an approach to interactive system development that aims to create a system that focuses on user needs and can increase user satisfaction. The final result of this UX design is a high-fidelity prototype. The prototype is then evaluated using the heuristic evaluation method involving three experts as evaluators. There are sixteen findings of usability problems after evaluation. After the evaluator consolidation process was carried out, there were ten problem findings that had to be fixed. The process of improving the solution design is carried out in accordance with the suggestions given by the evaluator